MANAGEMENT OF KNUCKLING WITH SCIATIC TOE BANDAGE IN A DOG - Prasad, A Arun; Das, B C; Niranjana, C; Kumar , R Suresh (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
Sciatic nerve deficit can occur as a result of spinal disease, trauma to the skeletal or peripheral nerve, or iatrogenic trauma. This is characterized by the loss of sensation with diminished or complete loss of conscious properioception which is manifested by knuckling or standing on the dorsum of the toes of hind foot. The dorsum of the toe get bruised, abarated and leading to sloughing of the foot due to repeated walking on the dorsum of the foot. Sciatic nerve deficit in a Spitz dog due to faulty injection at the thigh and its management is presented in this paper.